Anodic stripping voltammetry with graphite felt electrodes for the trace analysis of silver. Issue 15 (9th June 2016) - Davies, Trevor J.
Abstract : Graphite felt electrodes, costing less than one British pence each, are used as sensors for silver with a low limit of detection and large linear range. Abstract : Graphite felt (GF) is a mass produced porous carbon electrode material commonly used in redox flow batteries. Previous studies have suggested GF may have valuable applications in electroanalysis as a low cost disposable carbon electrode material, although most GF sensors have used flow cell arrangements. In this work, an elegant wetting technique is employed that allows GF electrodes to be used in quiescent solution to detect trace levels of silver in water via anodic stripping voltammetry. GF electrodes display good repeatability and a limit of detection of 25 nM of Ag + in 0.1 M HNO3, with a linear range spanning two orders of magnitude. This compares to a value of around 140 nM when using conventional carbon electrodes. Combined with their low cost and disposable nature, the results suggest GF electrodes can make a valuable contribution to electroanalysis.